Pengabdian Mahasiswa IAKN Toraja Melalui Kuliah Kerja Nyata Tematik di Lembang Salu Tapokko’, Tana Toraja - Serdianus, Serdianus; Ardano, Lucky; Biri, Agus; Bungin, Alfrida; Prinda, Almei; Bangun, Artin Sampe; Maviana, Anggryel; Asmiati, Asmiati; Tabuni, Delince; Mammai, Jandri; Bua, Janni Toding; Bumbungan, Kristin; Valengsa, Viola (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Diversity is an integral part of Indonesian society, often giving rise to conflicts that adversely affect the community. Therefore, through the implementation of the Thematic Real Work Lecture (KKN-T) in the Academic Year 2022/2023, the Research and Community Service Institute (LPPM) of IAKN Toraja focuses on the theme "Implementation of Religious Moderation in Social Action." The objective of KKN-T with this theme is to achieve a moderate community life amidst diversity. The method employed in this community service is field research with a qualitative approach. Data collection involves observation and documentation of the KKN-T student programs. The results of the community service indicate that the students have executed nine programs contributing to the realization of the KKN-T theme.